John Wamsley interviewed by Gregg Borschmann in the Environmental awareness in Australia oral history project - Wamsley, John, 1938-; Borschmann, Gregg (Gregg John), 1955- (1995)
Interview with the tireless, controversial and legendary Dr. John Wamsley of South Australia's Warrawong Sanctuary. Wamsley wants to fence off areas to protect Australia's native flora and fauna and rescue endangered species.
Digital master available
Uncorrected transcript (typescript, 133 leaves)
Keywords: Wamsley, John, -- 1938- -- Interviews; Wildlife conservation -- Australia; Biodiversity conservation -- Australia